2013
DOI: 10.1002/2013ja019415
|View full text |Cite
|
Sign up to set email alerts
|

Zonal flows and magnetic fields driven by large‐amplitude Rossby‐Alfvén‐Khantadze waves in the E‐layer ionosphere

Abstract: [1] Planetary-scale waves and vortices in the weakly ionized ionospheric E layer are dominated by the Hall conductivity that couples the Rossby and Alfvén dynamics giving rise to what are called Rossby-Alfvén-Khantadze electromagnetic structures. At finite amplitudes we show that the nonlinearities in the dynamics generate sheared zonal-flow velocities and zonal magnetic field fluctuations. The zonal-flow mechanism is based on the parametric excitation of the zonal variations through three-wave mode coupling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(55 reference statements)
1
8
0
Order By: Relevance
“…The basic assumptions, conditions, initial nonlinear system of equations, linear dispersion relation, zonal dispersion, zonal growth rate and excited magnetic field results for CIGA, CRK and CRAK are shown in table 1 and discussed in detail in Kaladze et al. (2012 a , b , 2013 a , b ) of our investigation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic assumptions, conditions, initial nonlinear system of equations, linear dispersion relation, zonal dispersion, zonal growth rate and excited magnetic field results for CIGA, CRK and CRAK are shown in table 1 and discussed in detail in Kaladze et al. (2012 a , b , 2013 a , b ) of our investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the values for the excited mean magnetic field become (see Kaladze et al. 2013 a , b for details).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear dynamics of CRAK EM planetary modes in the ionospheric E-layer is investigated (see details in [16] [30]). It is shown that under the prevalent action of Hall conductivity, owing to the latitudinal non-homogeneity of both the Coriolis parameter and stationary geomagnetic field, a new type of CRAK wave can propagate.…”
Section: Generation By Crak Wavesmentioning
confidence: 99%
“…Latitudinal inhomogeneity of both the Coriolis parameter and the geomagnetic field, and also caused by the gravitation so called stratification under the ionospheric conditions lead to the coupling of different electromagnetic (EM) planetary waves such as coupled Rosssby-Khantadze (CRK) [12] [13], Internal-Gravity-Alfven (CIGA) [14], Rossby-Alfven-Khantadze modes (CRAK) [15] [16] and drift-Alfven modes (CDA) [17] [18]. According to the nowadays presentations sheared zonal flows are created by the nonhomogeneous heating of the atmospheric layers by solar radiation.…”
Section: Introductionmentioning
confidence: 99%